High-field magnetoelasticity of Tm2Co17 and comparison with Er2Co17 - Andreev, A.V.; Zvyagin, A.A.; Skourski, Y.; Yasin, S.; Zherlitsyn, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Acoustic properties (ultrasound velocity and attenuation) and magnetostriction were measured in pulsed fields up to 60 T applied along the c axis of Tm2Co17 single crystal. Similar to Er2Co17, the transition in Tm2Co17 is accompanied by clear anomalies in the sound velocity. The observed 0.3% jump of the sound velocity at the transition is negative in Tm2Co17, whereas it is positive in Er2Co17. The magnetostriction at the transition also differs very much from that in Er2Co17. In Tm2Co17, the transition is accompanied by a smooth minimum of 0.15·10–4 in longitudinal magnetostriction whereas in Er2Co17 by a very sharp expansion of much largermagnitude (1.2·10–4). In the transverse mode, the effect in Tm2Co17 looks as very broad minimum of low amplitude (< 0.1·10–4) whereas in Er2Co17 as very sharp and large shrinkage (2.6·10–4). Thus, both themagnetoacoustics and magnetostriction are rather different in Tm2Co17 and Er2Co17. This supports different nature of the field-induced transitions in these compounds.